“Quero fazer…diz-me como começar.” : Oficinas de Expressão Plástica no 1º Ciclo do Ensino Básico - Botelho, Maria Ana Guerreiro (2019)
This dissertation unfolds around the assumption that the arts, namely, the Plastic/Visual Arts, play a decisive and irreplaceable role in Basic Education. Departing from a case study (based on a history of a teacher’s life), we intend to effectively demonstrate the role of artistic education as a means to: 1) the development of capacities and skills (creative, cognitive, emotional and social) of children in a cycle of education that is so fundamental and structuring of the future person and citizens; 2) improving the quality of education through relevant curricula and active pedagogies liable to capture the interest and enthusiasm of the students, including the involvement of local communities; 3) the existence of generalist teachers motivated and professionally trained to put into practice a comprehensive, integrated and interdisciplinary education. All this work stems from observations, experiences and knowledge accumulated over four decades by a teacher-trainer-researcher as professional within the field. The proposal for Plastic Expression Workshops in the 1st CEB outlined here stems, precisely, from accumulated findings on the ground and, in particular, aims to contribute (though modest and partially) to respond to problems and needs previously identified and continually expressed by generalist teachers: "I want to do ... Tell me how to start." The syllabus and teaching methodologies that make up these Workshops aims at strengthening the integration of Plastic Expression or Visual Arts in the curriculum of the 1st CEB in order to facilitate the learning of complex and cross-cutting themes tothe various disciplines, without the formers being subordinated to the role of mere ‘auxiliary’, on the contrary, underlining their own right as school disciplines. The research is supported by three documentary cores: a) textual and iconographic sources, personally built and accumulated over 40 years of teaching practice; b) personal teaching materials (disciplinary and interdisciplinary); c) legislation and programs by the ME; d) semi-structured interviews and testimonies (teachers and students). From the triangulation of sources emerged a gap between theory and practice: although the figure of the ‘specialist teacher’ is mandatory in legislation, on the ground its presence is not effective, which leaves the generalist teacher accountable in filling this vacuum. That is why we affirm the relevance and urgency of these Training Workshops, if we want to produce effective changes in the modes of teaching-learning at this level of education